Comparative Analysis of Electrical Performance of 50 WP Monocrystalline and Polycrystalline Solar Panels in Balikpapan - Ryan Effendi; Ahmad Zaki Syahwaludin; Gunawan Gunawan (G-Tech: Jurnal Teknologi Terapan, 2026)
The increasing demand for electrical energy, coupled with the depletion of fossil fuel resources and environmental concerns, has driven the need for renewable energy development. Solar energy, as one of the most abundant renewable resources in Indonesia, offers significant potential for sustainable electricity generation. This study aims to analyze and compare the electrical performance of 50 WP monocrystalline and polycrystalline solar panels in terms of voltage, current, power output, light intensity, and efficiency. The research was conducted experimentally on the rooftop of Universitas Balikpapan under clear weather conditions. Data were collected every 15 minutes from 09:00 to 13:00 WITA over several days. The measured parameters included solar irradiance, output voltage, output current, and power generation. The efficiency of each panel type was calculated based on the ratio of output power to input solar power. The results indicate that monocrystalline solar panels consistently produce higher efficiency and power output compared to polycrystalline panels under similar conditions. The findings of this study provide useful insights for selecting appropriate solar panel types for optimal energy generation in tropical regions such as Balikpapan.